Danhong injection attenuates doxorubicin-induced cardiotoxicity in rats via suppression of apoptosis: network pharmacology analysis and experimental validation - Yi, Xiaojiao; Wang, Fugen; Feng, Yan; Zhu, Junfeng; Wu, Yongjiang (Frontiers in Pharmacology, 2022)
Doxorubicin (DOX) is a potent chemotherapeutic agent against various types of human malignancies. However, the associated risk of cardiotoxicity has limited its clinical application. Danhong Injection (DHI) is a Chinese medicine with multiple pharmacological activities and is widely used for treating cardiovascular diseases. The aim of the present study was to evaluate the potential protective effect of DHI on DOX-induced cardiotoxicity in vivo and to investigate the possible underlying mechanisms. Firstly, a sensitive and reliable HPLC−ESI-Q-TOF-MS/MS method was developed to comprehensively analyze the chemical compositions of DHI. A total of 56 compounds were identified, including phenolic acids, tanshinones, and flavonoids. Then, a DOX-induced chronic cardiotoxicity rat model was established to assess the therapeutic effect of DHI. As a result, DHI administration prevented the reduction in body weight and heart weight, and improved the electrocardiogram performance. Additionally, the elevated levels of serum biochemical indicators were reduced, and the activities of oxidative enzymes were restored in the DOX-DHI group. Network pharmacology analysis further revealed that these effects might be attributed to 14 active compounds (e.g., danshensu, salvianolic acid A, salvianolic acid B, rosmarinic acid, and tanshinone IIA) and 15 potential targets (e.g., CASP3, SOD1, NOS3, TNF, and TOP2A). The apoptosis pathway was highly enriched according to the KEGG analysis. Molecular docking verified the good binding affinities between the active compounds and the corresponding apoptosis targets. Finally, experimental validation demonstrated that DHI treatment significantly increased the Bcl-2 level and suppressed DOX-induced Bax and caspase-3 expression in rat heart tissue. Furthermore, DHI treatment obviously decreased the apoptosis rate of DOX-treated H9c2 cells. These results indicated that DHI attenuated DOX-induced cardiotoxicity via regulating the apoptosis pathway. The present study suggested that DHI was a promising agent for the prevention of DOX-induced cardiotoxicity.